EMIC wave scale size in the inner magnetosphere: Observations from the dual Van Allen Probes. Issue 3 (13th February 2017) - Blum, L. W.; Bonnell, J. W.; Agapitov, O.; Paulson, K.; Kletzing, C.
Abstract: Estimating the spatial scales of electromagnetic ion cyclotron (EMIC) waves is critical for quantifying their overall scattering efficiency and effects on thermal plasma, ring current, and radiation belt particles. Using measurements from the dual Van Allen Probes in 2013–2014, we characterize the spatial and temporal extents of regions of EMIC wave activity and how these depend on local time and radial distance within the inner magnetosphere. Observations are categorized into three types—waves observed by only one spacecraft, waves measured by both spacecraft simultaneously, and waves observed by both spacecraft with some time lag. Analysis reveals that dayside (and H+ band) EMIC waves more frequently span larger spatial areas, while nightside (and He+ band) waves are more often localized but can persist many hours. These investigations give insight into the nature of EMIC wave generation and support more accurate quantification of their effects on the ring current and outer radiation belt. Key Points: EMIC wave active region scales are determined in the inner magnetosphere Multipoint Van Allen Probe measurements are used to disentangle spatial and temporal variations Dayside, H+ band waves occur over larger areas, while nightside, He+ band waves are more localized